Impact of sea level rise on estuarine salt water intrusion–A numerical model study for Changjiang Estuarine. Issue 1 (June 2020) - Song, Zekun; Shi, Weiyong; Zhang, Junbiao; Yuan, Di; Wu, Qingsong; Wang, Rusheng
Abstract: A 3D and high-resolution salinity transport numerical model of Changjiang Estuary with unstructured mesh was established using the MIKE3. The salinity transport model results were tested and verified by the observed data in Changjiang Estuary, the statistics of correlation coefficient are in good values. And then, the verified salinity transport model was used to study the impact of sea level rise on saltwater intrusion in the Changjiang Estuary. The results show that the entire North Branch was flooded with high saline water and a large amount of salt water spill over from the North Branch into the South Branch, which caused the South Branch with a high-low-high saddle-shaped distribution. With the rise of sea level, salt rocks such as the North Branch, the South Branch, and the North Channel moved upstream to varying degrees, strengthening the saltwater intrusion in the eastern Changjiang River. The high saline waters from North Branch spill over into South Branch also increased. The isohaline of North Branch South Branch and North Channel move to upstream, and move downstream in South Channel, North Passage and South Passage. The high salt water from the North Branch into the South Branch increased the salinity of the upper section of the South Branch.